Irrigation suitability and health risk assessment of groundwater resources in the Firozabad industrial area of north-central India: An integrated indexical, statistical, and geospatial approach - Saraswat, Anuj; Nath, Triyugi; Omeka, Michael E.; Unigwe, Chinanu O.; Anyanwu, Ifeanyi E.; Ugar, Samuel I.; Latare, Ashish; Raza, Md Basit; Behera, Biswaranjan; Adhikary, Partha P.; Scopa, Antonio; AbdelRahman, Mohamed A. E. (Frontiers in Environmental Science, 2023)
Abstract Firozabad city is one of the largest agricultural provinces in Uttar Pradesh saddled with intensive demand for water for irrigation. This has led to the over-exploitation of available groundwater resources and increased vulnerability of aquifers to contamination. In the present study, multiple water quality assessment indices, spatio-temporal, and statistical models were integrated to assess the suitability of fifty groundwater samples (n=50) within the area for irrigation and drinking, as well as the likely health risks from oral intake and dermal contact by inhabitants. Electrical conductivity, total hardness, sodium, chloride, and fluoride occurred in concentrations above the recommended standards; attributed to a high influx from agricultural and industrial wastewater. The pollution index of groundwater and water quality index revealed that 100% of the groundwater samples are extremely polluted; this was also supported by the joint multivariate statistical analyses. The majority of the irrigational water quality indices (sodium adsorption ratio, Kelly’s Ratio, permeability index, percent sodium) showed that the long-term use of the groundwater for irrigation in the area will result in reduced crop yield unless remedial measures are put in place. The health risk assessment showed that the children population is more predisposed to nitrate, chloride, and fluoride health risks from oral intake and dermal contact. Generally, risk levels from ingestion appear to increase in the western and north-eastern parts of the study area. From the findings of this study, it is highly recommended that adequate agricultural practices, land use, and water treatment regulatory strategies be put in place for water quality sustainability for enhanced agricultural production.